Radiation-Scattering–Integrated Design of Multi-Functional Metasurfaces Based on Antenna-Embedded Substrates - Fu, Xinmin; Fan, Ya; Han, Yajuan; Wang, Jiafu; Wang, Zhuangzhuang; Yan, Mingbao; Qu, Shaobo (Frontiers in Materials, 2022)
The integration of metasurface and antenna has brought new vitality to function integration and performance improvement for metasurfaces. In this paper, we propose a radiation-scattering-integrated (RSI) design method of functional metasurfaces by incorporating antenna radiators into the substrates. The antenna radiators can also be considered as a band-stop frequency selective surface (FSS) embedded within the dielectric substrate, which adds up to the degree of freedom (DOF) in tailoring electromagnetic (EM) properties of the substrate. In this way, not only radiation function is added to the metasurfaces, but also the original scattering-manipulation function is augmented. As an example, we apply this method to the design of a metasurface that can achieve high radiation gain in band and low-RCS out of band simultaneously. An antenna array was firstly designed, which uses circular patches as the radiators. Then, the antenna array was used as the substrate of a typical polarization conversion (PC) metasurface. The circular patch lies between the ground plane and the PC meta-atom, providing optimal electrical substrate thickness for PC at two separate bands. By adjusting structural parameters, the operating band of the antenna array can be made lie in between the two PC bands. In this way, the metasurface can simultaneously possess high-gain radiation function in band and high-efficiency PC function for RCS reduction out of band. A prototype fabricated and measured. Both the simulated and measured results show that the metasurface can achieve satisfactory radiation gain in band and significant RCS reduction out of band. This work provides an alternative method of designing multi-functional metasurfaces, which may find applications in smart skins, and others.